Volume Requirement Analysis of Beam Structure Work - Alfianarrochmah, Ilma; Fikri, Muhammad Nazhif Irsyal (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Beams serve as the main structural elements that transmit loads from floor slabs to columns and ensure the overall stability of the building. Calculation of beam volume requirements is essential to determine the amount of materials required, such as concrete and reinforcing steel. The conventional method of calculating the volume of a beam structure involves the use of basic mathematical formulas to calculate the dimensions and volume of materials required. This method is often used in the learning process of civil engineering to teach basic concepts of volume calculation. The method of implementing beam structure work affects the technical aspects. Therefore, it is necessary to conduct research related to the calculation of beam structure requirements in the Joglo Elementary School building construction project. The purpose of this research is to analyze the needs of bracing, formwork, and concreting on floors 1, 2, and 3 of the Joglo Elementary School Building Project. This type of research is quantitative research. The calculation uses conventional methods (mathematical formulas). The data collection method used is the field observation method and data processing is assisted using Microsoft Excel 2021 software. The need for beam formwork for the 1st floor is 12,492.12 kg, the 2nd floor is 28,222.35 kg, and the 3rd floor is 28,222.35 kg. The formwork requirements for the 1st floor beams amounted to 627.220 m2, the 2nd floor amounted to 873.91 m2, and the 3rd floor amounted to 873.91 m2. The need for concreting the 1st floor beam or tiebeam is 68,424 m3, the 2nd floor is 97,084 m3, and the 3rd floor is 97,084 m3.